IgA1 glycosylation is heritable in healthy twins - Lomax-Browne,HJ; Visconti,A; Pusey,CD; Spector,TD; Pickering,MC; Falchi,M; Cook,HT (Journal of the American Society of Nephrology, 2017)
IgA Nephropathy (IgAN) is the most common form of primary glomerulonephritis and an important cause of kidney failure. Characteristically, IgAN patients have increased serum levels of under-galactosylated IgA1 (gd-IgA1). We assessed the degree to which serum gd-IgA1 levels are genetically determined in healthy individuals. Serum IgA and gd-IgA1 level were determined by ELISA in a sample of 148 healthy female twins including 27 monozygotic and 47 dizygotic pairs. Using the classical twin model, the heritability of serum gd-IgA1 and IgA levels were 80% (95% CI: 66-89%) and 46% (95% CI: 15-69%) respectively. These data indicate that serum gd-IgA1 levels are highly heritable. Elucidating the genetic basis of this heritability will be important in understanding the pathogenesis of IgAN.